Typology of Anthroponymic Transformations in the Arabic, Georgian, and Greek Redactions of the "Story of Barlaam and Ioasaph" - Irma Makaradze (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2024)
This article examines the typology of anthroponymic transformations in the Arabic, Georgian, and Greek recensions of The Story of Barlaam and Ioasaph. The study aims to identify the mechanisms by which personal names are modified in the process of textual transmission and to determine the cultural and religious factors underlying these changes. The analysis is based on comparative, descriptive, cognitive-conceptual, and linguo-cultural methodologies. The findings demonstrate that, in the Georgian recension, anthroponyms frequently undergo a process of Christianisation: Arabic names are replaced either by biblical anthroponyms or by phonetically similar forms, likely created through association with biblical naming traditions. This tendency is particularly evident in cases where a given character is absent from the Arabic recension but appears in the Georgian and Greek versions under a newly introduced name. Conversely, in the Greek recension, anthroponyms found in the Georgian text that are only phonetically similar to biblical forms are rendered as exact biblical names. The results of the study reveal a gradual process of anthroponymic Christianisation (Arabic → Georgian → Greek) and confirm the intermediary role of the Georgian Balavariani within this transformation.